Diaphragm coating composition, coated diaphragm and lithium ion battery

By combining ceramic materials and non-fluoropolymer materials with specific proportions, combined with aqueous acrylic modified chlorinated polypropylene resin as binder, a composite separator coating composition is constructed, which solves the problems of poor heat resistance, poor adhesion and high thickness of the separator coating, and achieves the improvement of energy density and safety of lithium-ion batteries.

CN119842284APending Publication Date: 2025-04-18EVE ENERGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411987162.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the diaphragm coating has problems such as poor heat resistance, poor adhesion and large coating thickness, which is difficult to meet the energy density and lightweight requirements of lithium-ion batteries.

Method used

A composite membrane coating composition is constructed using a specific proportion of ceramic materials, non-fluoropolymer materials, and aqueous acrylic modified chlorinated polypropylene resin as binders, dispersants, wetting agents and water, and is coated onto the base film after baking and drying to form a thin and uniform coating.

Benefits of technology

It improves the heat resistance and bonding properties of the diaphragm coating, reduces the coating thickness, meets the energy density and safety requirements of lithium-ion batteries, and achieves environmentally friendly solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842284A_ABST
    Figure CN119842284A_ABST
Patent Text Reader

Abstract

The invention provides a diaphragm coating composition, a coated diaphragm and a lithium ion battery. The diaphragm coating composition is prepared from the following components in percentage by mass: 10.0 percent to 90.0 percent of a ceramic material, 5.0 percent to 30.0 percent of a non-fluorine polymer material, 1.0 percent to 10.0 percent of a binding agent, 1.0 percent to 5.0 percent of a dispersing agent, 0.05 percent to 0.5 percent of a wetting agent and 2.95 percent to 45.5 percent of water, wherein the binder is water-based acrylic acid modified chlorinated polypropylene resin. According to the present invention, the aqueous acrylic acid modified chlorinated polypropylene resin is particularly selected as the binder, such that the binding effect of the diaphragm coating and the base membrane can be improved while the binding property of the coating and the pole piece can be substantially improved so as to improve the overall energy density of the battery. In addition, the diaphragm coating composition disclosed by the invention can realize a high-efficiency mixed coating process, a thin and uniform coating is obtained, and the environment-friendly requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a diaphragm coating composition, a coated diaphragm, and a lithium-ion battery. Background Art

[0002] There are two main types of membrane coatings: one is a ceramic coating that can improve the heat resistance and mechanical strength of the membrane, and the other is a glue layer (mainly composed of organic polymers) that can provide adhesion to the interface surface and improve the hardness of the battery. A single coating cannot provide both properties at the same time, so the emergence of double-layer or even triple-layer composite coatings solves this problem well. However, this also leads to an increase in thickness, which cannot meet the current demand for thin and light membrane applications.

[0003] Therefore, it is crucial to develop a separator coating with high heat resistance, high adhesion and reduced coating thickness while meeting the energy density requirements of lithium-ion batteries. Summary of the invention

[0004] The main purpose of the present application is to provide a diaphragm coating composition and a coated diaphragm and a lithium-ion battery to solve the problems of poor heat resistance, poor adhesion and large coating thickness of the diaphragm coating in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a diaphragm coating composition is provided, which comprises, by mass percentage, 10.0% to 90.0% of a ceramic material, 5.0% to 30.0% of a non-fluoropolymer material, 1.0% to 10.0% of a binder, 1.0% to 5.0% of a dispersant, 0.05% to 0.5% of a wetting agent and 2.95% to 45.5% of water; wherein the binder is an aqueous acrylic acid-modified chlorinated polypropylene resin.

[0006] Furthermore, the acid value of the above-mentioned water-based acrylic acid modified chlorinated polypropylene resin is 20-100 mg KOH / g; and / or, the thermal weight loss starting temperature of the water-based acrylic acid modified chlorinated polypropylene resin is above 200° C.; and / or, the viscosity of the water-based acrylic acid modified chlorinated polypropylene resin is 1000-5000 mPa·s; and / or, the water content of the water-based acrylic acid modified chlorinated polypropylene resin is 40%-70%; and / or, the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid modified chlorinated polypropylene resin is 5-30:100.

[0007] Further, the wetting agent is an ether wetting agent, and / or the ether wetting agent is polyoxyethylene alkylphenol ether and / or fatty alcohol polyoxyethylene ether. Further, the dispersant is selected from any one or more of methyl amyl alcohol, isopropanol, ethylene oxide and ethylene glycol.

[0008] Furthermore, the ceramic material is alumina and / or boehmite, and the particle size of the ceramic material is 0.5 to 5 μm.

[0009] Furthermore, the non-fluoropolymer material is selected from any one or more of polymethyl methacrylate, meta-aramid, polyetherimide, polyimide, polyacrylic acid and polyurethane; and / or the non-fluoropolymer material is a microsphere having a particle size of 0.5 to 5 μm; and / or the molecular weight of the non-fluoropolymer material is 500,000 to 1.5 million.

[0010] According to another aspect of the present application, a coated diaphragm is provided, comprising a base film and a diaphragm coating, wherein the diaphragm coating is obtained by mixing the above-mentioned diaphragm coating composition, coating it on the surface of the base film, and then baking and drying it.

[0011] Furthermore, the above-mentioned base membrane is selected from any one or more of polyolefin base membranes, cellulose non-woven fabrics, PVDF porous membranes, and PI electrospun porous membranes; and / or the polyolefin base membrane is selected from any one or more of polyethylene membranes, polypropylene membranes, and polyethylene-polypropylene composite membranes; and / or the thickness of the base membrane is 2.5 to 25 μm; and / or the porosity of the base membrane is 30 to 40%.

[0012] Furthermore, the thickness of the diaphragm coating is 0.5-10 μm; and / or the coverage of the diaphragm coating is 25-85%.

[0013] According to another aspect of the present application, a lithium-ion battery is provided, comprising a separator, a positive electrode plate and a negative electrode plate, wherein the separator is the above-mentioned coated separator.

[0014] By applying the technical solution of the present application, the present application constructs a composite diaphragm coating composition by using a specific proportion of ceramic materials, non-fluoropolymer materials, binders, dispersants, wetting agents and water. Ceramic materials provide heat resistance and mechanical strength. Non-fluoropolymer materials enhance adhesion and flexibility, while also reducing pollution to the environment. Binders, dispersants and wetting agents work together to improve the bonding between materials and the uniformity of the coating. Water is used as a solvent to ensure the fluidity and processability of the slurry. Among them, the present application particularly selects water-based acrylic acid modified chlorinated polypropylene resin as a binder, which can improve the bonding between the diaphragm coating and the base film while further improving the bonding between the coating and the pole piece, thereby improving the overall energy density of the battery. In addition, the diaphragm coating composition disclosed in the present application can achieve a high-efficiency mixing process to obtain a thin and uniform coating, while having excellent heat resistance and bonding properties, and meeting environmentally friendly requirements, providing a solution for thinning the diaphragm, which is beneficial to improving the electrical performance and safety of the electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0016] Figure 1 A schematic structural diagram of a diaphragm provided in Example 1 of the present application is shown.

[0017] Among them, the above drawings include the following reference numerals:

[0018] 1. Base film; 2. Ceramic material; 3. Non-fluoropolymer material; 4. Binder. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0020] As analyzed in the background technology of this application, the diaphragm coating existing in the prior art has the problems of poor heat resistance, poor adhesion and large coating thickness. In order to solve the above problems, this application provides a diaphragm coating composition and a coated diaphragm and a lithium-ion battery.

[0021] In a typical embodiment of the present application, a diaphragm coating composition is provided, which comprises, by mass percentage, 10.0% to 90.0% of a ceramic material, 5.0% to 30.0% of a non-fluoropolymer material, 1.0% to 10.0% of a binder, 1.0% to 5.0% of a dispersant, 0.05% to 0.5% of a wetting agent and 2.95% to 45.5% of water; wherein the binder is an aqueous acrylic modified chlorinated polypropylene resin.

[0022] The present application constructs a composite diaphragm coating composition by using a specific proportion of ceramic materials, non-fluoropolymer materials, binders, dispersants, wetting agents and water. Ceramic materials provide heat resistance and mechanical strength. Non-fluoropolymer materials enhance adhesion and flexibility, while also reducing pollution to the environment. Binders, dispersants and wetting agents work together to improve the bonding between materials and the uniformity of the coating. Water is used as a solvent to ensure the fluidity and processability of the slurry. Among them, the present application particularly selects water-based acrylic acid-modified chlorinated polypropylene resin as a binder, which can improve the bonding between the diaphragm coating and the base film while further improving the bonding between the coating and the pole piece, preventing the diaphragm from falling off due to insufficient bonding ability during use, affecting the long-term electrical performance of the battery. In addition, the diaphragm coating composition disclosed in the present application can achieve a high-efficiency mixing process to obtain a thin and uniform coating, while having excellent heat resistance and bonding properties, and meeting environmentally friendly requirements, providing a solution for thinning the diaphragm, thereby helping to improve the electrical performance and safety of the electrochemical device.

[0023] In one embodiment of the present application, the acid value of the above-mentioned water-based acrylic acid modified chlorinated polypropylene resin is 20-100 mg KOH / g; and / or, the thermal weight loss starting temperature of the water-based acrylic acid modified chlorinated polypropylene resin is above 200° C.; and / or, the viscosity of the water-based acrylic acid modified chlorinated polypropylene resin is 1000-5000 mPa·s; and / or, the water content of the water-based acrylic acid modified chlorinated polypropylene resin is 40%-70%; and / or, the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid modified chlorinated polypropylene resin is 5-30:100.

[0024] The acid value reflects the content of free acidic functional groups in the water-based acrylic acid modified chlorinated polypropylene resin. For the acrylic acid modified chlorinated polypropylene resin, the acid value affects its bonding strength with ceramics and polymer materials. Therefore, limiting the acid value within the above range is conducive to improving the bonding strength of ceramic materials and non-fluoropolymer materials. The diaphragm coating needs to remain stable at high temperatures, and the thermal weight loss starting temperature of the resin is a key indicator. Therefore, limiting its thermal weight loss starting temperature within the above range is conducive to improving the stability of the diaphragm coating. The viscosity affects the fluidity of the slurry and the controllability of the coating process. Therefore, limiting its viscosity within the above range is conducive to improving the coating effect of the diaphragm coating. As a water-based resin, the control of water content is crucial for its viscosity and coating performance. Therefore, controlling its water content within the above range is conducive to improving the stability and efficiency of the diaphragm coating during the coating process. By controlling the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid modified chlorinated polypropylene resin within the above range, it is conducive to improving the stability and coating performance of the diaphragm coating composition. In addition, the water-based acrylic acid modified chlorinated polypropylene resin produced by Hemings Deqian (Shanghai) Chemical Co., Ltd. is preferred.

[0025] In one embodiment of the present application, the wetting agent is an ether wetting agent, and / or the ether wetting agent is selected from polyoxyethylene alkylphenol ether and / or fatty alcohol polyoxyethylene ether.

[0026] The wetting agent can enhance the uniformity of the coating and reduce the interface resistance. By controlling the type of the wetting agent within the above range, it is beneficial to improve the rheological properties of the diaphragm coating composition, thereby improving the uniform dispersion and tight adhesion of the coating material on the base film.

[0027] Wherein, preferred polyoxyethylene alkylphenol ether is polyoxyethylene nonylphenol ether wetting agent (Shandong Jinyueyuan New Material Co., Ltd.), and of course those skilled in the art can also select other specific types of polyoxyethylene alkylphenol ether, which will not be repeated here. Preferred fatty alcohol polyoxyethylene ether is dodecyl alcohol polyoxyethylene ether (Shandong Jinyueyuan New Material Co., Ltd.), and of course those skilled in the art can also select other specific types of fatty alcohol polyoxyethylene ether, which will not be repeated here.

[0028] In one embodiment of the present application, the dispersant is selected from any one or more of methyl pentanol, isopropanol, ethylene oxide and ethylene glycol.

[0029] Dispersants can promote uniform mixing of diaphragm coating materials, thereby improving the mechanical properties and heat resistance of the diaphragm coating. By controlling the type of dispersant within the above range, it is beneficial to optimize the dispersion performance of the coating composition, reduce the aggregation of ceramic and polymer particles, and thus improve the stability of the coating.

[0030] In one embodiment of the present application, the ceramic material is alumina and / or boehmite, and the particle size of the ceramic material is 0.5-5 μm.

[0031] The above ceramic material has an irregular morphology, which helps to improve its bonding with non-fluoropolymer materials and base membranes, and at the same time uses its excellent heat resistance and mechanical strength to improve the thermal stability of the diaphragm coating. By controlling the particle size of the ceramic material within the above range, it is helpful to reduce the shrinkage of the coating at high temperature and maintain the integrity of the diaphragm.

[0032] In one embodiment of the present application, the non-fluoropolymer material is selected from any one or more of polymethyl methacrylate, meta-aramid, polyetherimide, polyimide, polyacrylic acid and polyurethane; and / or the non-fluoropolymer material is a microsphere, and the particle size of the microsphere is 0.5 to 5 μm; and / or the molecular weight of the non-fluoropolymer material is 500,000 to 1.5 million.

[0033] By controlling the type, form, particle size and molecular weight of the non-fluoropolymer material within the above range, it helps to improve the adhesion between the diaphragm coating and the base membrane while greatly improving the adhesion between the diaphragm coating and the electrode, thereby improving the overall energy density of the battery. In addition, it is also beneficial to maintain the flexibility of the diaphragm coating while reducing pollution to the environment.

[0034] In another typical embodiment of the present application, a coated diaphragm is provided, comprising a base film and a diaphragm coating, wherein the diaphragm coating is obtained by mixing the above-mentioned diaphragm coating composition, coating it on the surface of the base film, and then baking and drying it.

[0035] The coated diaphragm obtained by coating the above-mentioned diaphragm coating composition on the surface of the base film after mixing and then baking and drying, not only improves the heat resistance and adhesion of the coated diaphragm, but also meets the environmental friendliness requirements, and also provides a solution for the thinning of the diaphragm, which is beneficial to improving the electrical performance and safety of the electrochemical device.

[0036] In addition, in order to further improve the comprehensive performance of the coated diaphragm obtained in the present application, in some embodiments of the present application, a method for preparing the coated diaphragm is also provided, comprising: step S1: fully stirring and mixing the ceramic material, the non-fluoropolymer material, the binder, the dispersant, the wetting agent and the pure water to obtain a diaphragm coating composition; step S2: coating the diaphragm coating composition on the surface of the base film and then baking and drying and winding treatment in sequence to obtain a coated diaphragm. The coating process is micro-gravure coating, and the baking and drying temperature is 50 to 70°C.

[0037] In one embodiment of the present application, the above-mentioned base membrane is selected from any one or more of polyolefin base membranes, cellulose non-woven fabrics, PVDF porous membranes, and PI electrospun porous membranes; and / or the polyolefin base membrane is selected from any one or more of polyethylene membranes, polypropylene membranes, and polyethylene-polypropylene composite membranes; and / or the thickness of the base membrane is 2.5 to 25 μm; and / or the porosity of the base membrane is 30 to 40%.

[0038] By controlling the type, thickness and porosity of the base film within the above range, it is beneficial to improve the ionic conductivity and mechanical strength of the diaphragm. Controlling the thickness of the base film within the above range is beneficial to meet the demand for thinner coated diaphragms. Controlling the porosity of the base film within the above range is beneficial to improve the bonding between the diaphragm coating and the base film, thereby improving the high efficiency and long life of the electrochemical device.

[0039] In one embodiment of the present application, the thickness of the diaphragm coating is 0.5-10 μm; and / or the coverage of the diaphragm coating is 25-85%.

[0040] By controlling the thickness and coverage of the diaphragm coating within the above range, the air permeability, mechanical strength and bonding properties of the coated diaphragm are improved, and the requirements of lightness and thinness are met, which is beneficial to improving the overall performance of the battery.

[0041] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a separator, a positive electrode plate and a negative electrode plate, wherein the separator is the above-mentioned coated separator.

[0042] The lithium-ion battery prepared using the above-mentioned coated diaphragm has significantly improved energy density, cycle performance and safety, and is suitable for high-demand applications such as 3C products and electric vehicles.

[0043] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] (1) Preparation of diaphragm

[0046] a. Selection of base film: Choose polyethylene base film with a thickness of 5 μm and a porosity of 30%.

[0047] b. Preparation of coating slurry: Calculated by weight percentage, 30% of aluminum oxide powder with a particle size of about 2 μm was added to deionized water and stirred for 60 minutes; 8% of polymethyl methacrylate powder with a particle size of about 1 μm was added thereto and stirred thoroughly for 60 minutes; 4% of water-based acrylic acid modified chlorinated polypropylene resin binder (Hemmingsdeqian (Shanghai) Chemical Co., Ltd., acid value of 60 mg KOH / g, thermal weight loss starting temperature of 220°C, viscosity of 3000 mPa·s, water content of 55%, mass ratio of water-based acrylic acid segment to chlorinated polypropylene resin segment of 20:100), 3% isopropanol dispersant and 0.1% polyoxyethylene nonylphenol ether wetting agent (Shandong Jinyueyuan New Materials Co., Ltd.) were added and stirred for 40 minutes to obtain a coating slurry.

[0048] c. Use the micro-gravure roller coating process, use a coating machine to evenly roll the prepared coating slurry onto the polyethylene diaphragm, bake and dry at 50°C, and roll it up for use to obtain the corresponding mixed coating diaphragm. The thickness of the diaphragm coating is maintained at 3.0±0.1μm. The diaphragm structure can refer to Figure 1 , wherein 1 represents a base film, 2 represents a ceramic material, 3 represents a non-fluoropolymer material, and 4 represents a binder.

[0049] (2) Preparation of lithium-ion batteries

[0050] The lithium cobalt oxide positive electrode sheet, graphite negative electrode sheet and the above-mentioned separator prepared according to the normal process are assembled into a battery cell through a winding process, and then injected with electrolyte for formation. The formation temperature is 80°C and the pressure is 10kg / cm 2 After formation, secondary sealing is performed to obtain the finished battery cell.

[0051] The finished battery cells are used to carry out rated capacity testing and cycle testing.

[0052] Example 2

[0053] The difference from Example 1 is that 1% of water-based acrylic acid-modified chlorinated polypropylene resin binder is added, and the amount of water is increased by 3%, and finally a finished battery cell is obtained.

[0054] Example 3

[0055] The difference from Example 1 is that 10% of water-based acrylic acid-modified chlorinated polypropylene resin binder is added, the amount of water used is reduced by 6%, and finally a finished battery cell is obtained.

[0056] Example 4

[0057] The difference from Example 1 is that the wetting agent is dodecyl alcohol polyoxyethylene ether (Shandong Jinyueyuan New Materials Co., Ltd.), and a finished battery cell is finally obtained.

[0058] Example 5

[0059] The difference from Example 1 is that 30% of boehmite powder with a particle size of about 2 μm is added to deionized water to finally obtain a finished battery cell.

[0060] Example 6

[0061] The difference from Example 1 is that the dispersant is ethylene oxide, and a finished battery cell is finally obtained.

[0062] Example 7

[0063] The difference from Example 1 is that a polyethylene film-polypropylene film composite film is selected with a thickness of 10 μm and a porosity of 30%, and finally a finished battery cell is obtained.

[0064] Example 8

[0065] The difference from Example 1 is that the acid value of the water-based acrylic acid-modified chlorinated polypropylene resin is 20 mg KOH / g, and a finished battery cell is finally obtained.

[0066] Example 9

[0067] The difference from Example 1 is that the acid value of the water-based acrylic acid-modified chlorinated polypropylene resin is 100 mg KOH / g, and a finished battery cell is finally obtained.

[0068] Example 10

[0069] The difference from Example 1 is that the acid value of the water-based acrylic acid-modified chlorinated polypropylene resin is 10 mg KOH / g, and a finished battery cell is finally obtained.

[0070] Embodiment 11

[0071] The difference from Example 1 is that the viscosity of the water-based acrylic acid-modified chlorinated polypropylene resin is 1000 mPa·s, and a finished battery cell is finally obtained.

[0072] Example 12

[0073] The difference from Example 1 is that the viscosity of the water-based acrylic acid-modified chlorinated polypropylene resin is 5000 mPa·s, and a finished battery cell is finally obtained.

[0074] Embodiment 13

[0075] The difference from Example 1 is that the viscosity of the water-based acrylic acid-modified chlorinated polypropylene resin is 800 mPa·s, and a finished battery cell is finally obtained.

[0076] Embodiment 14

[0077] The difference from Example 1 is that the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid-modified chlorinated polypropylene resin is 5:100, and a finished battery cell is finally obtained.

[0078] Embodiment 15

[0079] The difference from Example 1 is that the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid-modified chlorinated polypropylene resin is 30:100, and a finished battery cell is finally obtained.

[0080] Example 16

[0081] The difference from Example 1 is that the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid-modified chlorinated polypropylene resin is 4:100, and a finished battery cell is finally obtained.

[0082] Comparative Example 1

[0083] (1) Preparation of diaphragm

[0084] The difference between Comparative Example 1 and Example 1 is that the water-based acrylic acid-modified chlorinated polypropylene resin binder in Example 1 is replaced with a carboxymethyl cellulose binder, and the other process conditions are the same.

[0085] (2) Preparation of lithium-ion batteries

[0086] The finished battery cell is consistent with that in Example 1, and finally a finished battery cell is obtained.

[0087] Comparative Example 2

[0088] (1) Preparation of diaphragm

[0089] The difference between Comparative Example 2 and Comparative Example 1 is that the polymethyl methacrylate powder in Comparative Example 1 is replaced with PVDF powder, and the other process conditions are the same.

[0090] (2) Preparation of lithium-ion batteries

[0091] The same as comparative example 1 was maintained to finally obtain a finished battery cell.

[0092] Comparative Example 3

[0093] The difference from Example 1 is that 0.5% of water-based acrylic acid-modified chlorinated polypropylene resin binder is added, and the amount of water is increased by 3.5%, and finally a finished battery cell is obtained.

[0094] Comparative Example 4

[0095] Calculated by weight percentage, 8% of aluminum oxide powder with a particle size of about 2 μm is added to deionized water and stirred for 60 minutes; 4% of polymethyl methacrylate powder with a particle size of about 1 μm is added thereto and stirred for 60 minutes; 0.8% of aqueous acrylic acid modified chlorinated polypropylene resin binder, 3% of isopropanol dispersant and 0.1% of polyoxyethylene nonylphenol ether wetting agent (Shandong Jinyueyuan New Materials Co., Ltd.) are added and stirred for 40 minutes to obtain a coating slurry, and finally a finished battery cell is obtained.

[0096] The performance of the diaphragms and finished battery cells obtained in the above examples and comparative examples was tested. The temperature conditions of the cycle test of the battery cells were 25±3°C, the charging current was 1C, the discharging current was 0.5C, and the number of cycles was 500. The rate discharge current of the battery cells was 1C. The hot box test conditions of the battery cells were 130±2°C and the time was 1 hour;

[0097] Test method for air permeability growth rate: Use an air permeability tester to test 3 different positions along the TD direction of the membrane and take the average value. Test the air permeability of the base membrane before coating and the air permeability of the finished membrane after coating. Calculate the air permeability growth rate according to the air permeability growth rate = (finished membrane air permeability - base membrane air permeability) / base membrane air permeability.

[0098] The test method for dry pressing bonding strength is as follows: stack positive electrode sheets and diaphragms of a certain length and width, press them at 90°C for 10 minutes with a pressure of 1.0-1.2 MPa. Fix the electrode sheets and diaphragms of the obtained laminated samples at both ends of the tensile machine respectively, and stretch them at a speed of 20 mm / min for more than 100 mm to obtain the dry pressing bonding strength between the diaphragm and the electrode sheets.

[0099] The test method for volume energy density: After the battery cell is divided into different capacities, the capacity value and voltage are obtained. The energy value is calculated according to capacity value × voltage = energy value. The length, width and thickness of the battery cell are measured to calculate the volume. The ratio of energy value to volume is the volume energy density.

[0100] The test results are shown in Table 1 below:

[0101] Table 1

[0102]

[0103]

[0104] Among them, the test results of the hot box test conditions for the battery cell at 130°C for 1h are explained as follows:

[0105] In the data of the hot box test results at 130°C for 1h, the value before the “ / ” represents the number of cells that passed the test, and the value 20 after the “ / ” represents the total number of cells tested. Specifically, taking the test result 20 / 20 of Example 1 as an example, it means that 20 out of 20 tested cells are qualified; taking the test result 19 / 20 of Example 2 as an example, it means that 19 out of 20 tested cells are qualified and one is unqualified.

[0106] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:

[0107] The present application constructs a composite diaphragm coating composition by using a specific proportion of ceramic materials, non-fluoropolymer materials, binders, dispersants, wetting agents and water. Ceramic materials provide heat resistance and mechanical strength. Non-fluoropolymer materials enhance adhesion and flexibility, while also reducing pollution to the environment. Binders, dispersants and wetting agents work together to improve the bonding between materials and the uniformity of the coating. Water is used as a solvent to ensure the fluidity and processability of the slurry. Among them, the present application particularly selects water-based acrylic acid modified chlorinated polypropylene resin as a binder, which can improve the bonding effect between the diaphragm coating and the base film, while also further improving the bonding between the coating and the pole piece, and reducing the expansion rate of the battery cell during charging and discharging. In addition, the diaphragm coating composition disclosed in the present application can achieve a high-efficiency mixing process to obtain a thin and uniform coating, while having excellent heat resistance and bonding properties, and meeting environmentally friendly requirements, providing a solution for thinning the diaphragm, which is beneficial to improving the electrical performance and safety of the electrochemical device.

[0108] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A membrane coating composition, characterized in that: In terms of mass percentage, the diaphragm coating composition comprises: 10.0% to 90.0% ceramic materials; 5.0% to 30.0% non-fluoropolymer material; 1.0% to 10.0% binder; 1.0% to 5.0% dispersant; 0.05% to 0.5% wetting agent; 2.95% to 45.5% water; Wherein, the binder is water-based acrylic acid modified chlorinated polypropylene resin.

2. The diaphragm coating composition according to claim 1, characterized in that The acid value of the water-based acrylic acid modified chlorinated polypropylene resin is 20 to 100 mg KOH / g; and / or the thermal weight loss starting temperature of the water-based acrylic acid modified chlorinated polypropylene resin is above 200° C.; and / or the viscosity of the water-based acrylic acid modified chlorinated polypropylene resin is 1000 to 5000 mPa·s; and / or the water content of the water-based acrylic acid modified chlorinated polypropylene resin is 25% to 60%; and / or the mass ratio of the water-based acrylic acid segment to the chlorinated polypropylene resin segment in the water-based acrylic acid modified chlorinated polypropylene resin is 5 to 30:

100.

3. The diaphragm coating composition according to claim 1 or 2, characterized in that: The wetting agent is an ether wetting agent, and / or the ether wetting agent is polyoxyethylene alkylphenol ether and / or fatty alcohol polyoxyethylene ether.

4. The diaphragm coating composition according to any one of claims 1 to 3, characterized in that The dispersant is selected from any one or more of methyl amyl alcohol, isopropanol, ethylene oxide and ethylene glycol.

5. The diaphragm coating composition according to any one of claims 1 to 4, characterized in that The ceramic material is alumina and / or boehmite, and the particle size of the ceramic material is 0.5-5 μm.

6. The diaphragm coating composition according to any one of claims 1 to 5, characterized in that The non-fluorinated polymer material is selected from any one or more of polymethyl methacrylate, meta-aramid, polyetherimide, polyimide, polyacrylic acid and polyurethane; and / or the non-fluorinated polymer material is microspheres, and the particle size of the microspheres is 0.5 to 5 μm; and / or The molecular weight of the non-fluorine polymer material is 500,000 to 1.5 million.

7. A coated diaphragm, comprising a base film and a diaphragm coating, characterized in that: The diaphragm coating is obtained by mixing the diaphragm coating composition according to any one of claims 1 to 6, coating it on the surface of the base film, and then baking and drying it.

8. The coated diaphragm according to claim 7, characterized in that The base membrane is selected from any one or more of polyolefin base membranes, cellulose non-woven fabrics, PVDF porous membranes, and PI electrospun porous membranes; and / or the polyolefin base membrane is selected from any one or more of polyethylene membranes, polypropylene membranes, and polyethylene-polypropylene composite membranes; and / or the thickness of the base membrane is 2.5 to 25 μm; and / or the porosity of the base membrane is 30 to 40%.

9. The coated diaphragm according to claim 7, characterized in that: The thickness of the diaphragm coating is 0.5-10 μm; and / or the coverage of the diaphragm coating is 25-85%.

10. A lithium ion battery comprising a separator, a positive electrode sheet and a negative electrode sheet, characterized in that: The separator is the coated separator according to any one of claims 7 to 9.

Citation Information

Cited By

  • Battery diaphragm, preparation method thereof and secondary battery

    CN120261917A

  • Coating diaphragm, preparation method thereof and lithium ion battery

    CN121192366A

  • Coated separator, method for preparing the same, and lithium ion battery

    CN121192366B